Pengaruh Pemberian Pestisida Nabati Terhadap Intensitas Serangan Hama Penting pada Tiga Varietas Tanaman Kedelai (Glycine max (L.) Merrill) - Afifah, Putri Hasna; Wagiono, Wagiono; Adhi, Satriyo Restu (UNIVERSITAS LABUHANBATU, 2024)
Efforts to increase domestic soybean production are still hampered by the use of low-yielding varieties and pest attacks caused by high temperatures that are relatively stable throughout the year. This research aims to obtain botanical pesticides and varieties that produce the lowest intensity of important pest attacks on soybean plants (Glycine max (L.) Merrill). The research method used was a factorial Randomized Block Design (RBD) which consisted of 9 treatments and was repeated 3 times. The first factor is Variety which consists of 3 levels, namely v1 (Anjasmoro), v2 (Grobogan), v3 (Nusa Sanggabuana).The second factor is Botanical Pesticides which consists of 3 levels, namely p0 (Control), p1 (Kenikir Leaves), p2 (Soursop Leaves). The results of the analysis of variance and DMRT test at 5% level showed that There was an interaction effect between the type of botanical pesticide and three soybean varieties on the intensity of important pest attacks at plant age of 9 WAP. The independent factors of the varieties showed significant differences in plant height at 14, 21, 28 and 35 DAP and number of pods.Meanwhile, the independent factor of applying kenikir leaf botanical pesticides showed the highest value for the number of pods and the lowest intensity of pest attacks at ages 3, 5 and 7 WAPbut was not significantly different from other treatments. Keywords: soybean varieties, botanical pesticides, pests